Comparison of the Effects of Yucca saponin, Yucca schidigera, and Quillaja saponaria on Growth Performance, Immunity, Antioxidant Capability, and Intestinal Flora in Broilers - Zhenglie Dai; Huixian Wang; Jinsong Liu; Haoran Zhang; Qing Li; Xiaorong Yu; Ruiqiang Zhang; Caimei Yang (Animals, 2023)
The purpose of this study is to investigate the effects of Yucca saponin (YSa), Yucca schidigera (YS), and Quillaja Saponaria (QS) on growth performance, nitrogen metabolism, immune ability, antioxidant capability, and intestinal flora of yellow-feather broilers. This study randomly divided a total of 480 1-day yellow-feather broilers into 4 treatment groups. Factors in the 4 groups included CON group (basic diet), YSa group (basic diet mixed with 500 mg/kg YSa), YS group (basic diet mixed with 500 mg/kg YS), and QS group (basic diet mixed with 500 mg/kg QS). Throughout the 56-day study period, YSa, YS, and QS groups had higher average daily gain in broilers than the CON group (p < 0.01). The YS group had a lower feed gain ratio (F: G) in broilers than the CON group (p < 0.05). YSa, YS, and QS showed increased serum immunoglobin A (IgA), immunoglobin Y (IgY), immunoglobin M (IgM), and total antioxidant capacity (T-AOC) levels; enhanced acetic acid, butyric acid, and valeric acid levels of cecal content; and reduced contents of ammonia nitrogen, urea nitrogen, interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and malondialdehyde (MDA) in serum in broilers (p < 0.05). The relative abundance of Lachnoclostridium in the QS group was decreased compared with that in the CON group (p < 0.05). Higher IgA and IgY sera contents were observed in the YS group compared to the YSa and QS groups (p < 0.05). In contrast with the QS group, the serum IL-6 concentration of the YS group was reduced (p < 0.05). In conclusion, YSa, YS, and QS promoted growth performance, nitrogen metabolism, immunity, antioxidant capability, and intestinal flora in broilers. Through the comparison of YSa, YS, and QS, it was found that YS is more suitable as a feed additive to ameliorate the healthy growth of broilers.